PENGARUH SARANA DNA PRASARANA AKADEMIK TERHADAP MINAT BELAJAR MAHASISWA PENDIDIKAN EKONOMI STAMBUK 2023 - Sabrina Erisa Aulia Sihotang; Khairunnisa Umi Almas; Siti Mardiah; Dwi Atika Zahara; Eki Monalisa Surbakti; Yohanna Sitanggang; Mica Siar Meiriza (Politeknik Bisnis Indonesia, 2024)
Abstract Learning infrastructure and facilities are direct and indirect needs to improve the quality of learning and students' interest in learning. The reason the researcher conducted this research was that the researcher wanted to understand the extent of the impact of facilities and infrastructure on students' interest in learning in the 2023 Economic Education Stambuk; therefore, the researcher chose the research title